Study of p53 expression in premalignant squamous epithelial lesions of cervix - B., Divya; Nayak, Ashwini U.; Honappa, Sridhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Every year in India, 1,22,844 women are diagnosed with cervical cancer and 67,477 die from the disease. This study was done with the aim of studying the expression of p53 in pre-malignant squamous epithelial lesions of cervix. Methods: Patients coming to our institution who are undergoing biopsy for abnormal cytology/colposcopy were included in the study. Total of 39 patients were studied. Immunohistochemistry was used to study the p53 expression in cervical intra-epithelial lesions. Results: Out of 39 patients studied, p53 positivity was found in CIN 1 in38.5% cases, CIN 2 and CIN 3 in 80.75%. Conclusions: The present study has showed that p53 expression increased with increasing severity of Cervical intraepithelial neoplasia (CIN) and this fact can be used in clinical practice to identify those patients who require more surveillance.